Usus wa-Ru’á fī Tadrīs al-Lughah al-‘Arabīyah li-Ghayr al-Nāṭiqīna bi-hā - Sulaiman, Aisha Merghani Abdurrahim (Al-Ma‘rifah, 2019)
The research aims to explain (1) Teaching and disseminating the Arabic language among non-native speakers in a correct way; (2) Teaching language skills in a clear and integrated manner; (3) Choose the appropriate method of teaching; (4) Finding the most effective way to communicate the Arabic language to the whole world; (5) Keep the sounds of the Arabic language as is. Therefore, the researcher presents the problem of this research: the need of non-Arab societies for the Arabic language, and learning them in an often non-systematic way, which led to the spread of the language incorrectly. The results show that (1) Learners of the Arabic language in general, their education must be based on confirming the four language skills and their learners from non-native speakers in particular, it must be trained and practiced on these skills; (2) There is no complete and imperfect teaching method, but it is the educational position that imposes a certain type of method; (3) Some learners of the Arabic language who are not their children have reached a stage of mastery that may exceed their children. This is due to his keen desire to learn it. (4) The teacher of the Arabic language for non-native speakers of it must be broad-educated, familiar with the cultures of the people who study Arabic, to know the differences between the voices of the Arabic language and the sounds of the learner’s mother language, as well as the significance of the vocabulary that differs from one people to another.